1996
DOI: 10.1146/annurev.bi.65.070196.001125
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Helicase-Catalyzed Dna Unwinding

Abstract: DNA helicases are essential motor proteins that function to unwind duplex DNA to yield the transient single-stranded DNA intermediates required for replication, recombination, and repair. These enzymes unwind duplex DNA and translocate along DNA in reactions that are coupled to the binding and hydrolysis of 5'-nucleoside triphosphates (NTP). Although these enzymes are essential for DNA metabolism, the molecular details of their mechanisms are only beginning to emerge. This review discusses mechanistic aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
578
0
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 732 publications
(593 citation statements)
references
References 13 publications
12
578
0
3
Order By: Relevance
“…Knipper's group (12,15,16) has reported that MCM4, -6, and -7 proteins form a stable complex and that MCM2 protein is more loosely associated with the trimeric form of MCM proteins. My conclusion that a hexamer of MCM4, -6, and -7 has DNA helicase activity is consistent with the findings that several helicases including SV40 T antigen (30) function as a hexamer (31)(32)(33). However, a possibility that protein(s) bound to MCM proteins has intrinsically the DNA helicase activity cannot be ruled out.…”
Section: Fig 3 Protein Cross-linking Of MCM Proteins a The Pooledsupporting
confidence: 79%
“…Knipper's group (12,15,16) has reported that MCM4, -6, and -7 proteins form a stable complex and that MCM2 protein is more loosely associated with the trimeric form of MCM proteins. My conclusion that a hexamer of MCM4, -6, and -7 has DNA helicase activity is consistent with the findings that several helicases including SV40 T antigen (30) function as a hexamer (31)(32)(33). However, a possibility that protein(s) bound to MCM proteins has intrinsically the DNA helicase activity cannot be ruled out.…”
Section: Fig 3 Protein Cross-linking Of MCM Proteins a The Pooledsupporting
confidence: 79%
“…The theoretical limit on efficiency of unwinding is thus 9-12 bp unwound per ATP hydrolysis. Experimentally measured values are typically smaller, usually 0.33-1 bp unwound/ATP hydrolyzed [2]. For PcrA, the measured efficiency of unwinding is approximately 1 bp unwound/ATP [11].…”
Section: Helicase Propertiesmentioning
confidence: 97%
“…The average number of base pairs unwound before the helicase falls off the NA is known as the processivity; measured values for different types of helicases vary from 40 to 30,000 bases unwound [2]. Both the rate and the processivity of a helicase are strongly affected by the presence of accessory proteins as well as solution conditions.…”
Section: Helicase Propertiesmentioning
confidence: 99%
“…Table 1 compares solubility free energy increments (SFEI=-RTdlnS 2 /dC 3 ; Eq. 1) for effects of selected Hofmeister salts (and HCl) on solubility of aliphatic and aromatic hydrocarbons (for the complete data set, see Table S1); [2][3][4][5][6][7]33,35 representative data for benzene are shown in Fig. 1A.…”
Section: Analysis Of Salt Effects On Model Compound Solubility Using mentioning
confidence: 99%
“…[1][2][3][4][5] At moderate to high salt concentrations (> 0.1 M), osmotic effects (dependent on the number of ions per formula unit but otherwise nonspecific) and ion-specific effects (traditionally called Hofmeister effects) are most significant, while Coulombic effects (valence-specific but otherwise nonspecific) dominate at relatively low salt concentrations. Processes that expose biopolymer surface to the aqueous salt solution (e.g.…”
Section: Introductionmentioning
confidence: 99%